The Impact of Finnair's CSR Activities on Its Brand Performance - Soukupová, Kateřina; Olšanová, Květa; Procházka, Petr; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2022)
Understanding corporate social responsibility (CSR) is crucial. CSR brings many advantages, from better brand reputation to revenue improvement. In this thesis, a conceptual framework is proposed to investigate the impact of Finnair's CSR activities on its brand performance. Brand performance, in this case, is defined as customer-based brand performance and measured by four indicators: brand satisfaction, brand loyalty, perceived quality and brand trust. Data was collected from Finnair's customers through a thorough questionnaire. In order to test the model, hypotheses were set and further investigated by conducting MANOVA. Following the MANOVA results, the model was proved sufficient, and dependent variables were found significant (Pillai's V = .206, F(4,141) = 9.139, p < .001, partial η2 = .206). Our research shows that Finnair's CSR activities positively impact each customer-based brand performance indicator presented, so it can be said that Finnair's CSR activities positively impact its brand performance. The presented study provides additional evidence of CSR and its positive impact on brand performance in the aviation industry.
Vedoucí práce: Květa Olšanová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses